2010
DOI: 10.1007/s13187-010-0120-z
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students Educate Teens About Skin Cancer: What Have We Learned?

Abstract: Skin cancer is a serious societal problem, and public awareness outreach, including to youth, is crucial. Medical students have joined forces to educate adolescents about skin cancer with significant impacts; even one 50-min interactive outreach session led to sustained changes in knowledge and behavior in a cohort of 1,200 adolescents surveyed. Medical students can act as a tremendous asset to health awareness public outreach efforts: enthusiastic volunteerism keeps education cost-effective, results in expone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 8 publications
0
16
0
3
Order By: Relevance
“…Sun-protection behavior and attitude begin at a young age, therefore, it is important to heighten the awareness in adolescents. [7] Individual, who develop such skills at a young age and more likely to adopt and sustain healthy lifestyle during the rest of their life. Since children and adolescents are an important target group for skin cancer prevention, developing comprehensive programs including physical, social, and organizational environments that promote UVR protection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun-protection behavior and attitude begin at a young age, therefore, it is important to heighten the awareness in adolescents. [7] Individual, who develop such skills at a young age and more likely to adopt and sustain healthy lifestyle during the rest of their life. Since children and adolescents are an important target group for skin cancer prevention, developing comprehensive programs including physical, social, and organizational environments that promote UVR protection.…”
Section: Introductionmentioning
confidence: 99%
“…[7111213] However, in Turkey, there are limited studies with primary school students in the Western part[1415] of the country in health services, vocational schools,[16] and university students. [17] This indicated that attitudes and behaviors of students are related to Sun-protection were not sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…“Medical students represent a vast and efficient source of enthusiasm and energy for public outreach endeavors” (Kamell et al, , p. 154). There are valuable resources in medical students who could be recruited as volunteer health educators in outreach programs.…”
Section: Discussionmentioning
confidence: 99%
“…There are valuable resources in medical students who could be recruited as volunteer health educators in outreach programs. By researching and teaching others about different health topics, students are provided an opportunity to engage in service‐learning experiences, apply and improve their content knowledge, and heighten their awareness of these topics (Kamell et al, ; Olm‐Shipman, Reed, & Christian, ; Robak et al, ; Wong & Naguwa, ). A majority of medical students participating in the survey reported accessing quality information resources through PubMed, UpToDate, DynaMed, AccessMedicine, MD Consult, Micromedix, and MedlinePlus.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions for this notoriously difficult-to-reach target population have to date had minimal success (Table 1). [8][9][10][11] It has been postulated that this is due to a sense of adolescent invincibility, lack of internalization and lack of transfer of knowledge into positive behaviour in adolescents. 12 The SunSafe Student Ambassador Program (SSSAP) was launched in 2018 by the Melanoma Institute Australia (MIA) with the intent to improve knowledge about melanoma, and to improve the attitudes and behaviours of high-school students towards sun safety through the peer-to-peer learning environment, given that peer attitudes and behaviours constitute a significant predictor of individual risk-taking behaviours.…”
Section: Introductionmentioning
confidence: 99%